(untitled) (Journal of Computational Intelligence and Robotics, 2022)
Quantum sensing technologies have emerged as promising tools for biomedical applications, offering unprecedented sensitivity and precision in detecting biomolecules, imaging tissues, and monitoring physiological parameters. This paper reviews the recent advancements and challenges in leveraging quantum sensing technologies for biomedical purposes. We discuss the principles behind quantum sensing, including quantum entanglement and quantum superposition, and how they enable enhanced sensing capabilities. We then explore various biomedical applications, such as early disease detection, drug development, and personalized medicine, highlighting the potential impact on healthcare. Additionally, we examine the current challenges, including scalability, cost-effectiveness, and integration with existing medical systems, and propose potential solutions. Overall, this paper provides insights into the transformative potential of quantum sensing technologies in revolutionizing biomedical research and healthcare.